Спільнота сільської молоді в Литві: соціальне і культурне формування мужності та жіночності під час обрядодій річного календарного циклу - Шакніс, Ж. (Народна творчість та етнологія, 2011)
The purpose of this article to reveal gender-based differences within the annual cycle by examining youth behaviour differences coming to light during calendar and work celebrations in the second half of 19th. and first half of 20th. c.